2022
DOI: 10.3389/fvets.2022.818827
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Prolactins on the Development of the Uterus in Neonatal Mice

Abstract: The endometrial gland is one of the most important components of the mammalian uterus. However, few studies have been conducted on the regulatory mechanisms of adenogenesis during the development of endometrium. In the present study, we detected the genes expression of 35 different prolactin family members (PRLs) together with the prolactin receptor (PRL-R) in the endometrium of neonatal mice along with the adenogenesis process, to address which prolactin-like genes play a key role during gland development in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…As for PRL7C1, we do not have the means to measure plasma concentration. There is no report of PRL7C1 function, except one study that suggests PRL7C1 involvement in neonatal uterus development [76]. Simmons et al showed a slight increase in Prl7c1 mRNA level in the G18.5 mouse placenta [15].…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
“…As for PRL7C1, we do not have the means to measure plasma concentration. There is no report of PRL7C1 function, except one study that suggests PRL7C1 involvement in neonatal uterus development [76]. Simmons et al showed a slight increase in Prl7c1 mRNA level in the G18.5 mouse placenta [15].…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
“…Additionally, IGF1 and IGF2, which are downstream targets, are involved in regulating cellular growth and differentiation (69). The significance of prolactin family members in uterine development and endometrial adenogenesis has been well established (70).…”
Section: Role Of Adenogenesis In Endometriosismentioning
confidence: 99%